2017
DOI: 10.2139/ssrn.3054752
|View full text |Cite
|
Sign up to set email alerts
|

Does Inequality Foster or Hinder the Growth of Entrepreneurship in the Long-Run?

Abstract: This article assesses the extent to which historical levels of inequality affect the creation and survival of businesses over time. To this end, we use the Global Entrepreneurship Monitor (GEM) survey across 66 countries over 2005-2011. We complement this survey with data on income inequality dating back to early 1800s and current institutional environment, such as the number of procedures to start a new business, countries' degree of financial inclusion, corruption and political stability. We find that althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…All these economic data are taken from World Bank, except for income inequality which comes from United Nations 14 . The inclusion of such country features is common in comparative entrepreneurship research to rule out alternative explanations (e.g., Estrin et al, 2013; Gutiérrez‐Romero & Méndez‐Errico, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…All these economic data are taken from World Bank, except for income inequality which comes from United Nations 14 . The inclusion of such country features is common in comparative entrepreneurship research to rule out alternative explanations (e.g., Estrin et al, 2013; Gutiérrez‐Romero & Méndez‐Errico, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…These simple poverty decompositions, theoretically underpinned by Lorenz Curve principles, can be empirically estimated. Extensive research has shown that inequality is in particular detrimental for poverty reduction since increases in GDP are often captured by middle or upper classes, with a limited trickledown effect for the poor (Gutiérrez-Romero & Méndez-Errico, 2017;Ravallion, 2005;van der Weide & Branko, 2018). In our empirical analysis, we extend these decomposition regressions to include the potential role of financial inclusion in poverty reduction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The supply-side approach sees inequality as a precondition for entrepreneurship on the premise that income and wealth inequality creates a class of people wealthy enough to absorb the high risks associated with investing in new ventures and products (Atems and Shand 2018;Bylund 2016;Jones and Kim 2018;Packard and Bylund 2017). In contrast, the demand-side argument claims that by increasing the budgetconstrained population and reducing social mobility, inequality reduces both the economy's purchasing power and the human and financial capital endowments necessary for business creation and success (Auguste 2020;Gutiérrez-Romero and Méndez-Errico 2017;Perry-Rivers 2016;Xavier-Oliveira, Laplume, and Pathak 2015).…”
Section: Introductionmentioning
confidence: 99%